Effect of cold conditions on double poling sprint performance of well-trained male cross-country skiers - Wiggen, Ø. N.; Waagaard, S. H.; Heidelberg, C. T.; Oksa, J. (The Journal of Strength and Conditioning Research, 2013)
This study compared the effects of cold (-14° C) and moderate environments (6° C) on double poling (DP) sprint performance. Wearing modern cross-country ski racing suits, 14 highly trained male cross-country skiers performed a test protocol on a DP ergometer, consisting of a standardized warm-up followed by a 30-second maximal sprint (DP30s) and a 2-minute maximal sprint (DP2min), and after an 8-minute recovery period, another DP30s and DP2min were performed. Finally, the participants performed an incremental DP test to exhaustion. We observed no difference between rectal temperature in cold and moderate conditions. Mean skin temperature (Tskin) was lower in the cold condition; the lowest values being 20.3° C at -14° C and 27.0° C at 6° C. Power output decreased between the first and the second DP30s under both conditions, but the reduction was 4.9% (p < 0.05) greater in the cold condition. Power output decreased by 4.8% (p < 0.05) between the first and second DP2min at -14° C, but we found no difference at 6° C. In the incremental test to exhaustion, there was a 7.2% (p < 0.05) reduction in peak power output and a 7.8% (p < 0.05) lower peak oxygen consumption at -14° C. In conclusion, this study demonstrated that DP sprint performance was lower at -14° C than at 6° C. Tskin and body temperature were lower at -14° C. This may indicate cooling of superficial musculature and may explain the reduced DP sprint performance observed in our study.